The Persian-Byzantine conflict on Syria in the Mid seventh century AD - Sakkour, Braah; Sulieman, Seba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Syria has suffered in the ancient history of the many conflicts that have at home, and represents a conflict between the Persian Empire and the Byzantine Empire one of the most important and longest of these conflicts that have to control the most important cities such as Damascus and Edessa and Akadds.othml Arabs living there the horrors of those conflicts and suffered a lot, the Persian Empire has taken Arabs in Iraq Manathira shield shielding them Byzantines attacks as well as from the Byzantines took Ghassanid living in Syria shield shielding them Persians attacks and have been associated with them Bohlav and treaties. This situation continued until the Muslim conquest of Syria where he entered in the first Arab-Islamic state.